Effect of Firm-Specific Attributes on Environmental Accounting Disclosure. Evidence from Firms Listed in the Nairobi Securities Exchange, Kenya - Tarus, J. Kipngetich (African Journal of Education,Science and Technology (AJEST), 2020)
The main objective of this study was to examine the effect of firm-specific attributes on environmental accounting disclosure in Kenya. The study was driven by legitimacy theory and a longitudinal research design was adopted. The study targeted 27 listed firms at Nairobi securities Exchange from 2008 to 2017. Findings showed that asset tangibility (β = .10, ρ<.05) and capital intensity (β = .42, ρ<.05) had a positive and significant effect on environmental accounting disclosure. The study concludes that asset tangibility, capital intensity, and ownership concentration are key predictors of environmental accounting disclosure. Therefore, firms need to diffuse ownership concentration and increase asset base, so as to increase the level of environmental accounting disclosure.